Late Complications Following Continuous-Flow Left Ventricular Assist Device Implantation - Grimm, Joshua C.; Magruder, J. Trent; Kemp, Clinton D.; Shah, Ashish S. (Frontiers in Surgery, 2015)
Left ventricular assist devices have become standard therapy for patients with end-stage heart failure. They represent potential long-term solutions for a growing public health problem. However, initial enthusiasm for this technology has been tempered by challenges posed by long-term support. This review examines these challenges and out current understanding of their etiologies.